Neuropathic and cAMP-induced pain behavior is ameliorated in mice lacking CNGB1. (July 2020) - Kallenborn-Gerhardt, Wiebke; Metzner, Katharina; Lu, Ruirui; Petersen, Jonas; Kuth, Miriam S.; Heine, Sandra; Drees, Oliver; Paul, Mandy; Becirovic, Elvir; Kennel, Lea; Flauaus, Cathrin; Gross, Tilman; et al.
Abstract: Cyclic nucleotide-gated (CNG) channels, which are directly activated by cAMP and cGMP, have long been known to play a key role in retinal and olfactory signal transduction. Emerging evidence indicates that CNG channels are also involved in signaling pathways important for pain processing. Here, we found that the expression of the channel subunits CNGA2, CNGA3, CNGA4 and CNGB1 in dorsal root ganglia, and of CNGA2 in the spinal cord, is transiently altered after peripheral nerve injury in mice. Specifically, we show using in situ hybridization and quantitative real-time RT-PCR that CNG channels containing the CNGB1b subunit are localized to populations of sensory neurons and predominantly excitatory interneurons in the spinal dorsal horn. In CNGB1 knockout (CNGB1 −/− ) mice, neuropathic pain behavior is considerably attenuated whereas inflammatory pain behavior is normal. Finally, we provide evidence to support CNGB1 as a downstream mediator of cAMP signaling in pain pathways. Altogether, our data suggest that CNGB1-positive CNG channels specifically contribute to neuropathic pain processing after peripheral nerve injury. Highlights: CNG channel expression is up-regulated after peripheral nerve injury. The CNG channel subunit CNGB1 is expressed in sensory neurons and in spinal dorsal horn neurons. CNGB1-deficient mice display reduced neuropathic pain behavior and altered electrophysiology after peripheral nerve injury. CNGB1-deficient mice show attenuated cAMP-induced pain behavior.